Productividad acumulada y su relación genética con características reproductivas en hembras brahman - Orlando Duitama, C. [UNESP]; Luis González, H.; Garcia, Diogo [UNESP]; Farah, Michel [UNESP]; Da Fonseca, Ricardo [UNESP] (My University, 2013)
Objective. Assessment of genetic parameters for accumulative productivity trait (ACP) and genetic correlations with age at first calving (AFC), between calving interval of first and second parity (BCI1) and longevity (LONG). Materials and methods. 8584 Brahman female records were used with an animal model in multi-trait analysis with restricted maximum likelihood method, implemented using the WOMBAT software. The models considered the fixed effects of contemporary group, parity and weaning weight of first calf covariate, the only random effect was the genetic additive direct. Weaning weight (P240) was included to reduce the effect of selection on the estimation of variance components. Results. The heritability estimates were 0.3±0.04, 0.11±0.03, 0.07±0.03 and 0.24±0.04 for AFC, BCI1, LONG and ACP respectively. Correlations between ACP and the other features were moderate to high and favorable. Conclusions. ACP can be included in breeding programs for Brahman, and used as selection criteria for its moderate heritability and genetic correlation with reproductive traits.
Accumulated productivity and its genetic association with reproductive traits in females brahman
Keywords: Beef cattle; Genetic parameters; Heritability; Reproductive efficiency (Source: CAB; Usda)